Analysis and design of a permanent magnet linear synchronous motor based on inductance calculation - Yucel, Enes; Mutluer, Mümtaz; Çunkaş, Mehmet (Archives of Electrical Engineering (Online), 2025)
This paper presents a comprehensive design and analysis methodology for a Permanent Magnet Linear Synchronous Motor (PMLSM), with a focus on evaluating different inductance modeling approaches. The motor design begins with analytical dimensioning based on defined design parameters. A two-dimensional finite element analysis follows this in ANSYS Maxwell to verify magnetic saturation, back-EMF, flux linkage, and electromagnetic performance under full load conditions. The inductance parameters are calculated using both conventional and look-up table (LUT) based models. In the conventional model, seven different methods are tested under static and dynamic conditions, as well as in nonsalient and salient scenarios, and their results are compared. In the LUT model, currentdependent inductance values are extracted from flux linkage maps. The motor designed in Maxwell, along with the calculated inductance data, is integrated into a dynamic cooperative simulation (co-sim) model controlled by an inverter in Simplorer to analyze the thrust force. The results show that the LUT model provides outputs that are closer to the co-sim reference than the traditional model. Furthermore, performance curves based on the Maximum Torque Per Ampere strategy are generated, and the force-speed and power-speed characteristics derived from both inductance models are compared. The findings emphasize the importance of accurate inductance modeling in capturing the actual electromagnetic behaviour of PMLSM under dynamic operating conditions.